Genetic analysis and molecular mapping of the purple leaf sheath in barley (Hordeum vulgare) - Demeke B. Mewa; Ann Caspersen; Jason D. Fiedler; Gongshe Hu; Dongying Gao (The Plant Genome, 2025)
Abstract Although anthocyanin is frequently found in various barley organs, the genetic basis of the pigmentation is still poorly understood. In this study, we examined the development of anthocyanin in GemCraft, a malting barley cultivar showing purple leaf sheath (PLS), and found that the pigmentation became visible on the leaf sheath at the early tillering stage. This study employed single nucleotide polymorphism (SNP) array genotyping data in two F2 populations developed using GemCraft and two barley lines with green leaf sheath throughout the plant development. Genetic and quantitative trait locus (QTL) analyses suggested regulation of the purple pigment accumulation by a single major QTL that was inherited as a dominant allele, which was necessary for the phenotype to develop. A major QTL, named qPLS2 (purple leaf sheath2 locus), was found on chromosome 2H and explained >70% of the trait variation. Nonetheless, the genetic model in the two mapping populations resonated between multiple loci and a single locus that determines the trait variation. Accordingly, in one of the populations, three minor QTL were also detected on chromosomes 1H and 5H: each of these QTL explained <5% variation and showed influence in regulation of the purple pigment intensity. In the qPLS2 QTL interval, comparative genomic analysis of annotated genes that are widely known to regulate anthocyanin development in plants identified a single candidate gene encoding a basic helix–loop–helix (bHLH) transcription factor. The study identified a new major QTL associated with the purple leaf sheath and generated further information for validation and cloning the causal gene for effective utilization of anthocyanin in barley genetic improvement.